Frugal innovations: a multidisciplinary review & agenda for future research - Dabić, Marina (2022)
Frugal innovation is about achieving more value while using fewer resources. This concept has found application across multiple domains, ranging from healthcare and transport to energy and manufacturing. This straddling of multidisciplinary domains fragments our academic understanding of the literature in this field. This state-of-the-art literature review, performed using multiple correspondence analyses across 199 articles, along with a Delphi study of prolific authors and practitioners working on frugal innovation, integrates multidisciplinary academic literature to offer a holistic picture of the current scholarly literature, outlining its key theoretical approaches and providing a glimpse of the future of the field. This study outlines the relevance of frugal innovations in combating the COVID-19 pandemic, establishing the key areas for future research in frugal innovation, such as new product development, ease of use, the performance of frugal innovations, strategy, and sustainability, among others.